1981
DOI: 10.1111/j.1749-6632.1981.tb33781.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Correlation of Clinical Course and Acetylcholine Receptor Antibody in Patients With Myasthenia Gravis

Abstract: Antibodies (Ab) to acetylcholine receptors ( AchR) are instrumental in bringing about the neuromuscular defect in myasthenia gravis (MG) . The demonstration of Ab by immunoprecipitation assay proved to be highly specific, of great diagnostic value, and in good correlation to clinical improvement in MG patients on plasma exchange therapy.l, Only little information is available in the long term correlation between intraindividual AB titers and clinical course.2 This study presents a group of 99 MG patients (41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…Other patients either did not show an impairment of neuromuscular transmission or their clinical state did not allow them to carry out the measurement (three cases). The decrement that attained maximal values of -10 to -57% in the total group changed by at least 10% (maximum change 30%/-) in 10 cases.…”
mentioning
confidence: 85%
“…Other patients either did not show an impairment of neuromuscular transmission or their clinical state did not allow them to carry out the measurement (three cases). The decrement that attained maximal values of -10 to -57% in the total group changed by at least 10% (maximum change 30%/-) in 10 cases.…”
mentioning
confidence: 85%
“…The first ordinal rating scale for MG (“MG Score”) was developed in the 1980s 52–54. The MG‐Score was a standardized outcome instrument that measured endurance of outstretched limbs and of neck lift, time to development of ptosis and dysconjugate gaze, eye closure strength, degree of grip strength decrement measured using a dynamometer, vital capacity, and frequency and severity of symptoms of chewing and swallowing fatigue and weakness 52–54. A slightly modified MG numerical scale was used as one of the primary outcome measures in a trial that demonstrated the efficacy of cyclosporine in MG 55, 56.…”
Section: Mg‐specific Ordinal Rating Scalesmentioning
confidence: 99%
“…[52][53][54] The MG-Score was a standardized outcome instrument that measured endurance of outstretched limbs and of neck lift, time to development of ptosis and dysconjugate gaze, eye closure strength, degree of grip strength decrement measured using a dynamometer, vital capacity, and frequency and severity of symptoms of chewing and swallowing fatigue and weakness. [52][53][54] A slightly modified MG numerical scale was used as one of the primary outcome measures in a trial that demonstrated the efficacy of cyclosporine in MG. 55,56 This scale was modified once more in the late 1990s, notably by replacing subjective assessments of speech and swallowing taken from the history with more objective tests of counting aloud to 50 and swallowing 4 ounces of water (Supporting Table 3). 57 The cyclosporine trials 55,56 and QMG interrater reliability testing [57][58][59] suggested that a three-point change in QMG score should be considered significant.…”
Section: Mg-specific Ordinal Rating Scalesmentioning
confidence: 99%
“…The current quantitative MG scoring system (QMG Score) is an expansion and modification of the tool developed by Besinger et al 12,13 (Table 2). The original scoring system consisted of 8 items, each graded 0 to 3, with 3 being the most severe.…”
Section: Quantitative Mg Scorementioning
confidence: 99%